Quality of life and patient‐reported toxicities in patients with advanced Merkel cell carcinoma treated with combined nivolumab and ipilimumab with or without stereotactic body radiation therapy - Aasha I. Hoogland; Andrew S. Brohl; Brent J. Small; Lauren Michael; Evan Wuthrick; Zeynep Eroglu; Dukagjin Blakaj; Claire Verschraegen; Nikhil I. Khushalani; Heather S. L. Jim; Sungjune Kim (Cancer Medicine)
Abstract Background Merkel cell carcinoma is a rare skin cancer associated with poor survival. Based on a previous Phase II trial of adults with advanced Merkel cell carcinoma by Kim and colleagues (2022), there is now a strong rationale for combination therapy (i.e., nivolumab and ipilimumab) to become a treatment option for patients with advanced Merkel cell carcinoma. The goal of this paper was to report on the secondary outcome of quality of life (QOL) among patients on this trial. Methods Patients receiving combined nivolumab and ipilimumab, with or without stereotactic body radiation therapy (SBRT), completed the European Organisation for Research and Treatment of Cancer (EORTC) QLQ‐C30 prior to starting treatment and every 2 weeks thereafter. Changes in QOL during treatment and post‐treatment were evaluated using piecewise random‐effects mixed models. Exploratory analyses compared changes in QOL between study arms. The original trial was registered with ClinicalTrials.gov (NCT03071406). Results Study participants (n = 50) reported no changes in overall QOL (ps > 0.05), but emotional functioning improved during treatment (p = 0.01). Cognitive and social functioning worsened post‐treatment (ps < 0.01). In general, patients treated with combination therapy only (n = 25) reported no change in QOL over time, whereas patients also treated with SBRT (n = 25) consistently demonstrated worsening QOL post‐treatment. Conclusion QOL is generally preserved in patients treated with combination therapy, but the addition of SBRT may worsen QOL. Combined with clinical efficacy data published previously, results support the use of combination therapy with nivolumab and ipilimumab as a treatment option for patients with advanced Merkel cell carcinoma.